Review of Fast Algorithms and Hardware Implementations on Computer Holography - Shimobaba, Tomoyoshi; Kakue, Takashi; Ito, Tomoyoshi (IEEE transactions on industrial informatics, 2016)
This study reviews fast algorithms and hardware implementations of computer holography, including computer-generated holograms and digital holography. To reduce the calculation time, which is mainly consumed by diffraction calculation, fast algorithms and hardware implementations are highly necessary and will ensure the further development of this field.